COVID-19: Evaluation and diagnosis - Govind Benkatti; Vinayak Patki (Wolters Kluwer Medknow Publications, 2020)
Rapid and accurate COVID-19 diagnostic testing is essential for controling the ongoing COVID-19 pandemic. Evaluation and diagnosis of COVID-19 infection is done on the basis of the clinical suspicion and appropriate laboratory tests. The current gold standard for COVID-19 diagnosis is real-time reverse transcription-polymerase chain reaction detection of SARS-CoV-2 from nasopharyngeal swabs. The World Health Organization, Centre for Disease control and Indian Council of Medical Research has published various guidelines about the scientific use and interpretation of results. Recently rapid antibody testing has also been recommended for clusters with influenza-like illness. These laboratory tests have their own limitations about their sensitivity and specificity; clinician has to interpret the results in the light of clinical condition of patient with suspected COVID-19 infection. Health-care provider should take due precautions while collecting, packaging, and transport of these samples. One has to adhere strictly to the guidelines published by the Government authorities in the diagnosis of these patients.